Human Resource Management Transformation in the Digital Age: Recent Trends and Implications - Wahdaniah; Riska Sucianti; Elizabeth Ambalele; Andi Herman Tellu (MultiTech Publisher, 2023)
This article examines the transformation of human resource management (HRM) in the evolving digital era. The main focus is integrating advanced technologies such as automation, Artificial Intelligence (AI), and digital platforms in HR management. Also discussed are changes in the role of HR managers, which now require skills in managing technology and analyzing data and adaptive abilities in responding to changing employee needs and industry trends. Emphasis is also placed on the importance of continuous development and training for employees to keep up with technological developments. The article also highlights an organization's readiness for change, including updating policies, restructuring, and retraining. From this analysis, it is concluded that the transformation of HR management in the digital era brings both opportunities and challenges and demands an integrated and adaptive approach from the organization.